2002
DOI: 10.1542/peds.109.6.e94
|View full text |Cite
|
Sign up to set email alerts
|

Noncompliance With Medical Follow-up After Pediatric Intensive Care

Abstract: ABSTRACT. Objectives. To describe the medical follow-up ordered, the health care utilization, the appointment compliance, and the risk factors associated with noncompliance in patients who are discharged after a pediatric intensive care unit (PICU) stay.Methods. A prospective, analytic, cohort study of 111 critically ill children, age 1 day to 16 years, who were admitted to a 30-bed PICU in an urban, tertiary-care, pediatric teaching hospital compared children who were compliant with medical follow-up with tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
37
3
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 18 publications
2
37
3
1
Order By: Relevance
“…Reasons for loss to follow-up were multifactorial and most commonly attributable to psychosocial factors such as access to transport, financial limitations, and parental self-reports of anxiety or depression. Our data is consistent with previous evidence suggesting that patients lost to follow-up may be systematically sicker (29, 30). Such information raises important concerns as to whether these patients are at greater risk of impaired functional recovery, highlights the need for further research in this area, and the need to optimize a follow-up plan to capture such patients in future studies.…”
Section: Discussionsupporting
confidence: 93%
“…Reasons for loss to follow-up were multifactorial and most commonly attributable to psychosocial factors such as access to transport, financial limitations, and parental self-reports of anxiety or depression. Our data is consistent with previous evidence suggesting that patients lost to follow-up may be systematically sicker (29, 30). Such information raises important concerns as to whether these patients are at greater risk of impaired functional recovery, highlights the need for further research in this area, and the need to optimize a follow-up plan to capture such patients in future studies.…”
Section: Discussionsupporting
confidence: 93%
“…Another explanation for this association could be that the parents of very young children are less likely to work outside the home, thus eliminating one potential barrier to outpatient follow-up frequently cited by parentsVparental work obligations. 6,11,16,26 Finally, it is possible that parental factors such as comfort level, experience, and personal confidence in dealing with a pediatric illness, all factors that commonly increase as the child grows older, influenced the likelihood of the parent to obtain outpatient follow-up for his/her child.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have measured attendance at follow-up appointments using a conceptual approach that implies that the root of the problem is lack of compliance on the part of care givers, rather than systematic difficulties that lead to delayed or inadequate follow-up. One study found that 28% of children discharged from paediatric (not neonatal) intensive care did not receive timely medical follow-up 9. Most published research on this transition in paediatric patients focuses on the effect of insurance on follow-up or describes early discharge programmes.…”
Section: Introductionmentioning
confidence: 99%